P=(-5, 2) Q=(-3, 6)
Good evening,
Answer:
Step-by-step explanation:
(6-2)÷((-3)-(-5))=2.
:)
The value of the expression when x = 6 is
Answer:
-21.
Step-by-step explanation:
(6)2-7(6)+9
--> 6x2= 12
--> 7x6= 42
Rewrite the expression:
--> 12-42+9
Solve:
--> 12-42= -30
--> -30+7= -21
midpoint =
The distance from -21 to 18 would be 39 units ( -21 to 0 is 21 and from 0 to 18 is 18 , 21 +18 = 39)
To find the midpoint distance, divide the total distance by 2:
x = 39/2
x = 19.5
Now to find the midpoint, either add 19.5 to -21 or subtract 19.5 from 18.
Midpoint = -1.5
Answer:
−1½ = x
Step-by-step explanation:
First, find the range in between 18 and −21, which is 39:
Take half of that range, then add that to −21:
I am joyous to assist you anytime.
Step-by-step explanation:
hi I have answered ur question
To make n the subject of the formula t = square root of n+3/n, we can isolate the square root term by squaring both sides of the equation and rearranging the equation to make n the subject.
To make n the subject of the formula t = √(n+3)/n, we can start by isolating the square root term. To do this, we square both sides of the equation:
t2 = √(n+3)/n2
Next, we can multiply both sides by n2 to get rid of the denominator:
t2n2 = n + 3
Finally, we can rearrange the equation to make n the subject:
n = (t2n2 - 3)/t2
#SPJ3